The Role of Rural Women in Decision Making Process in Arid Rajasthan - Saha, D K; Rani, Usha (Annals of Arid Zone, 2016)
An attempt has been made to study the role of rural women in decision making processes of various socio-economic activities. In decision making processes especially in agriculture, livestock and socioreligious matters, women were consulted by the heads of households. However, in some activities the role of women in decision making processes differ as indicated by the Friedman (Xr2) test. By and large, little difference in decision making processes between different groups establish homogeneous character of the population.